Let u = x + a
du/dx = 1
y = cos u
dy/du = - sin u = - sin (x + a)
dy / dx = (dy / du) . (du / dx)
dy / dx = - sin ( x + a )
2007-03-04 18:40:19
·
answer #1
·
answered by Como 7
·
0⤊
0⤋
Like cos(x), but with x+a, because x and x+a share the derivative 1.
d/dx cos(x+a) = -sin(x + a)
2007-03-04 18:41:07
·
answer #2
·
answered by Amit Y 5
·
0⤊
0⤋
set u= sin^3x and v= tan4x then calculate the by-product of each so u' = 3sin^2xcosx and v'= 4sec^2(4x) chain rule provides uv'+vu' so that you get (sin^3x)(4sec^2(4x))+ (tan(4x))(3sin^2xcosx) which will properly be simplified to sin^2(x) (3 cos(x) tan(4 x)+4 sin(x) sec^2(4 x))
2016-12-05 06:26:30
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
If a is simply a number and not a variable, then the derivitive is:
-sin(x+a)
let u=x+a
du=dx
so,
d/dx(cos(u))=-sin(u)
=-sin(x+a)
2007-03-04 18:40:35
·
answer #4
·
answered by Digital Olive 2
·
0⤊
0⤋
cos(x+a) *assuming a is a constant*
derivative of f(g(x)) = f'(g(x))*g'(x)
-sin(x+a)*(1)
-sin(x+a)
2007-03-04 18:42:54
·
answer #5
·
answered by Brian 3
·
0⤊
0⤋
let y = x + a
we get
d/dx(cos y) = -sin y dy/dx = - sin y . 1 or - sin y = - sin(x+a)
2007-03-04 18:41:00
·
answer #6
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
differentiate cos(x+a) with respect to (x+a) and differentiate (x+a) with respect to x. thats it
the answer is -sin(x+a) assuming "a" is a constant.
2007-03-04 18:40:54
·
answer #7
·
answered by buddy2smartass 2
·
0⤊
0⤋
o= cosx i= x+a
o'= -sinx i'= 1
-sin(x+a) * 1
2007-03-04 19:28:14
·
answer #8
·
answered by kjf e 2
·
0⤊
0⤋
f(x)=cos(x) ===> f'(x)= -sin(x)
g(x)=x+a ===> g'(x) = 1
your function h(x)=cos(x+a)=cos(g(x))=f(g(x))
h'(x)=g'(x)f'(g(x)) = (1) [-sin(x+a)] = -sin(x+a)
2007-03-04 18:40:12
·
answer #9
·
answered by v_arbab 1
·
0⤊
0⤋